Season-of-birth bias in association football - Simmons, C.; Paull, G. C. (Journal of Sports Sciences, 2001)
In this longitudinal study, we assessed the frequency of birth dates for boys selected for the Football Association National School. Birthdays were divided into three periods of the year: January to April, May to August and September to December. We compared data over a 5 year period and concluded that there is indeed a bias towards selecting older children. Furthermore, analysis of separate data revealed a shift of bias when comparing two different start dates, namely September and January. Our findings show that the youngest children from the January start date (born September to December) are selected significantly more often than the youngest children from the September start date (born May to August). Interestingly, even when the influence of body mass was reduced, the selection bias towards the older players remained.